Earnings Management and Corporate Governance Issues in the Banking and Finance Sector: A Review of Literature - Kumari, Prity; Pattanayak, J. K. (Prabandhan: Indian Journal of Management, 2015)
Focusing on the impact of earnings management and the importance of corporate governance mechanism, this study aimed at reviewing the existing literature available on earnings management and its association with corporate governance mechanism. In this paper, an attempt was made to establish a relationship between earnings management and corporate governance mechanisms in case of firms representing the banking and finance sector. From the review of existing literature, we attempted to develop a framework and get a direction for further research work in this area.